2005
DOI: 10.1111/j.1365-2842.2005.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of luting agents and reconstruction techniques on the fracture resistance of pre‐fabricated post systems

Abstract: Fracture resistance and fracture modes of endodontically treated maxillary central incisors restored with different post-and-core systems covered with all-ceramic copings were evaluated. Ten samples were prepared for each group. Groups 1, 2 and 3 consisted of tooth-coloured post-and-core, zirconia post (Cosmopost) with a composite core (Tetric Ceram), zirconia post (Cosmopost) with a custom made ceramic core (Cosmo Ingot), glass fibre-reinforced post (FRC Postec) with a composite core (Tetric Ceram), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
4
27
0
6
Order By: Relevance
“…On the other hand, exceptions were found in some of the studies reviewed. One study by Toksavul et al 46) reported higher fracture strength with a composite core (497.5 N) than with a ceramic core (474.6 N), although there was no statistically significant difference. Similarly, Wan et al 47) found no significant differences in the fracture strength of zirconia posts when used with ceramic and composite cores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, exceptions were found in some of the studies reviewed. One study by Toksavul et al 46) reported higher fracture strength with a composite core (497.5 N) than with a ceramic core (474.6 N), although there was no statistically significant difference. Similarly, Wan et al 47) found no significant differences in the fracture strength of zirconia posts when used with ceramic and composite cores.…”
Section: Resultsmentioning
confidence: 99%
“…Fracture strength The fracture strength of zirconia posts was evaluated using natural teeth in 15 studies 12,14,33,39,[41][42][43]48,49,51,55,58,[60][61][62] ( Table 1) and artificial roots in three studies 29,53,59) , and according to core material (composite resin core versus ceramic core) in nine studies 35,40,[44][45][46][47]52,54,57) (Table 2). Table 1 shows that the fracture strengths of teeth with zirconia posts and composite cores ranged between 300 N and 700 N. However, when ceramic cores were used, these values ranged between 800 N and 1500 N. These results concurred with studies which evaluated the fracture strength of zirconia posts according to core material 35,40,44,45,54) .…”
Section: Resultsmentioning
confidence: 99%
“…According to some authors 22,40 , the cervical third is the region which has more propensity to fracture in intra-radicular post restored teeth, particularly in those with reduced periodontal support. High von Mises equivalent stress levels encountered at the apical end of the posts in both models seem to suggest that the geometry of the post in this extremity can contribute to the stress state acting there.…”
Section: Discussionmentioning
confidence: 99%
“…Beyaz, translusent veya opak olmak üzere 3 temel renk tonunda ilk defa 1992 yılında geliştirilmişlerdir (15,27,32). Bu postların elastik modülleri düşük olduğu için mekanik özellikleri dentine karbon fiberlere göre daha yakındır.…”
Section: Cam Fiber Ile Güçlendirilmiş Kompozit Postunclassified
“…Işık geçirgenliği vardır (32). Bükülme dayanımı dentine benzerdir ve stresleri geniş yüzey alanlarına dağıtırlar (15,32).…”
Section: Cam Fiber Ile Güçlendirilmiş Kompozit Postunclassified